Lariat RNA debranching prevents harmful siRNA burst in plants - Qi Tang; Chenxi Ding; Xiaotuo Zhang; Taiyun Wang; Mengjie Zhu; Ruixue Cui; Wenya Yang; Jinbiao Ma; Guodong Ren; Xiaoming Zhang; Binglian Zheng (Science, 2026)
Lariat RNAs are formed from introns during pre–messenger RNA splicing, after which they are degraded by the debranching enzyme DBR1. Impairment of DBR1 leads to developmental arrest, yet the mechanism remains unclear. In this study, we found that debranching of lariat RNA prevents production of 21- and 22-nucleotide lariat-derived small interfering RNAs (lasiRNAs), which causes a burst of exonic siRNAs, thereby safeguarding development and defense response. LasiRNA biogenesis relied on RNA-dependent RNA polymerases and Dicer-like proteins (DCLs). Upon pathogen infection and dysfunction of DBR1, many lariat RNAs were hijacked by DCL4 and DCL2 and processed into siRNAs that particularly target immunity genes, ultimately disrupting plant defense responses. Collectively, DBR1-mediated lariat RNA removal serves as a protective mechanism to prevent the activation of a small RNA–based defense system in plants.